ENHANCING STUDENT ENGAGEMENT, TEACHER SELF-EFFICACY, AND PRINCIPAL LEADERSHIP SKILLS THROUGH MORNING MEETING IN AN ONLINE LEARNING ENVIRONMENT - Barnes, Daniel (East Carolina University, 2021)
This study examined the experiences of educators in a small, rural elementary school who provided live instruction in an online setting during the COVID-19 pandemic. The scholarly practitioner collaborated with inquiry partners to enhance student engagement, teacher self-efficacy, and principal leadership skills by implementing Morning Meeting, a social and emotional learning program from Responsive Classroom®, when students participated in remote online learning. The scholarly practitioner used over four decades of research about efficacy and identified leadership strategies and approaches that assisted in building individual and collective teacher efficacy so that teachers could effectively engage students. Behavioral, emotional, and cognitive engagement were identified in research and used by teachers to determine the quality of participation in Morning Meeting. Teachers took daily and weekly attendance to measure engagement, and the scholarly practitioner facilitated team meetings with groups of teachers to compile comments and statements regarding student engagement. These statements were coded using pre-selected codes based on research about types of student engagement. The scholarly practitioner facilitated the administration of a pre-study and post-study Teacher Self-Efficacy Scale so that individual, grade-span, and full-school efficacy data could be compiled. In addition, the scholarly practitioner held team meetings with the teachers to compile comments and categorize those statements into four areas: job accomplishment, skill development, social interaction, and coping with job stress. These four areas were also coded using the four categories described on the Teacher Self-Efficacy Scale. The scholarly practitioner also maintained a journal using a self-reflection tool about the lived experiences before, during, and after the study. The emphasis on this journal was about the development and growth of leadership skills, and the categories were pre-coded using Bernard Bass's categories of transformational leadership: individualized consideration, inspirational motivation, idealized influence, and intellectual stimulation. Student engagement increased throughout the study, and 77 percent of students were fully engaged during the study. Teachers expressed an increase in collective efficacy at the conclusion of the study, and six of the eight teachers reported individual increases in efficacy. The scholarly practitioner's use of differentiation within the context of transformational leadership was observed most frequently in the study.
Keywords: Collective Teacher Efficacy; Student Engagement; Morning Meeting; Leadership Skills; Transformational Leadership; Collaborative Action Research; Web-based instruction; Educational leadership; Teacher effectiveness; Rural schools; COVID-19 Pandemic, 2020- --Social aspects; Distance education; Elementary school teachers--Attitudes